Unravelling the structural‐property relations of porphyrinoids with respect to photo‐ and electro‐chemical activities. Issue 1 (12th December 2021) - Singh, Gita; Chandra, Sudeshna
Abstract: Porphyrins have multiple roles in living and nonliving systems because of their exceptional tunable chemical and physical properties. They are interesting macrocyclic compounds that could be modified in a number of ways. The structural diversity of porphyrinoids make them a unique choice for functional devices exhibiting photo‐ and electrochemical properties. Their properties can be modified or altered by either protonating the nitrogen atoms or by inducing charge transfer to the metal center. Structural changes induced by flattening and planar distortions, redox reactions, solvents, and porphyrin aggregations also influence the photo‐ and electro‐chemical properties of porphyrinoids. This review gives a brief explanation on the effects of structural orientation, molecular structure, and charge on the properties of porphyrinoids. The review also illustrates the correlation between the geometrical features and the photo‐ and electrochemical behavior of porphyrinoids. Abstract : Porphyrins are a set of tetrapyrrolic macrocycles, and interestingly with this underlying structural theme, porphyrins lead to an expanded diversity of biochemical functions. Because of the structure of porphyrins, the chemistry widens broadly beyond the scope of this review with limitless additional synthesis methods.